FACTORS AFFECTING EARLY COMPLEMENTARY FEEDING OF MOTHERS WITH BABIES AGED 0-6 MONTHS - nataningtyas, Candra Dewinataningtyas; Kumalasari, Dian; Kurniasari, Mia Ashari; Putri, Ellatyas Rahmawati Tejo (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Exclusive breastfeeding for babies from 0 to 6 months of age and continued until 2 years of age can promote healthy growth and development. According to the WHO, in 2020, if a child receives complementary foods before 6 months of age, their growth will be delayed, and the risk of diarrhea is 17 times higher and the risk of upper respiratory tract infection is 3 times higher. The problem of this study is that the rate of early complementary food distribution for babies aged 0–6 months is still high. This study aims to determine factors affecting early complementary feeding for babies from 0 to 6 months of age. Method: The design of this research is descriptive with a cross-sectional approach. The research was carried out in July–September 2023 in Banaran Village, Kediri East Java, with a sample of 32 respondents consisting of mothers with babies aged 0–6 months who had been given early complementary feeding. Sampling is done by consecutive sampling. The variables in this study are factors that influence the provision of early complementary feeding for mothers with babies aged 0–6 months. Data was obtained through direct interviews with respondents using a questionnaire. Results: This study showed that the factors affecting early complementary feeding are socio-cultural factors with high category (81.3%), knowledge level factors with medium category (50%), personal factors with low category (87.6%) and promotional advertising for infant formula and baby food have medium category (71.9%). Conclusion: research results shows that the factors affecting early complementary feeding for babies from aged 0-6 months are socio-cultural factors, personal factors, and promotional advertising factors.